Scientific Publication in Nursing and Midwifery in Iran - Reza Negarandeh (Tehran University of Medical Sciences, 2013)
Production of knowledge in nursing and midwifery is essential to develop body of knowledge and improve quality of health care. In recent years, growth rate of scientific publication in Iran was significant as it could be considered as a scientific jihad. Although everyone is proud of this accomplishment, an important question remaining in nursing and midwifery is that how the pace of scientific publication in these fields is consistent with the pace of scientific publication in other scientific fields. This editorial tries to answer this question. Through searching the Scopus for Iranian papers during 2008-2012 articles, I found 1063 articles in nursing and midwifery indexed in the Scopus. The number of articles was almost doubled per year within the last five years, excluding 2012. It implies coordination of scientific publication in nursing and midwifery with rapid growth of total scientific activities in other scientific fields in the country. On the other hand, findings showed that only 29 articles (2.7%) published by Iranian nursing and midwifery researchers were review articles. While, in the UK, 13.5% of articles in nursing and midwifery was review articles. This finding along with the importance of review articles as credible scientific evidence for clinical decision-making and improving management procedures shows the necessity of writing review articles by senior researchers in Iran. Comparing nationality of authors between Iranian articles with the UK articles showed that only 154 Iranian articles (about 10%) had a non-native author while, in the UK articles, about half of the articles had non-English collaborating authors. This finding reveals the necessity for further efforts to international studies. Through searching the Pubmed and Web of Science for Iranian articles during 2008-2012, we found 390 and 174 Iranian articles, respectively. The lower rate of articles indexed in these two databases, comparing to the Scopus, indicates the necessity of designing and conducting high quality studies and submitting articles in journals indexed in these two databases. Writing articles which observe principles of scientific writing in proper English language can increase the probability of acceptance of articles in more valid journals. Indexing Iranian nursing and midwifery journals in authoritative indexes can increase the rate of scientific publication. It requires more attention of administrators and editors of Iranian scientific journals to this critical issue.